Determination of urinary N-acetyl-?-D glucosaminidase (NAG) levels in experimental blunt renal trauma - Hanbeyolu, Alpaslan; Kazez, Ahmet; Ustundag, Bilal; Akpolat, Nusret (Turkish Assoc Trauma Emergency Surgery, 2011)
BACKGROUND We evaluated the applicability of urinary N-acetyl-beta-D glucosaminidase (NAG) levels in the diagnosis and follow-up in blunt kidney injury. METHODS Twenty Sprague-Dawley rats were studied. In the Sham group, left kidney exploration was made. In the Trauma group, after left kidney exploration, a 20 g weight was dropped onto the kidneys. Urine was collected for analysis with strip and determination of urinary NAG and creatinine (Cr) levels at baseline and 0-6, 12-24, 24-36 and 36-48 postoperative hours. Mann-Whitney U and Kruskal-Wallis tests were used. RESULTS Macroscopic examinations of traumatized kidneys revealed grade II and III injury, and histopathological examinations showed relevant changes. Macroscopic hematuria was observed in all traumatized rats. Urinary NAG/Cr levels in the Trauma group were found to be significantly higher than their base levels at 0-6, 12-24, 24-36, and 36-48 hours. In the Sham group, only the level of NAG/Cr at 0-6 hours was significantly higher. The increase in NAG/Cr levels at 0-6 hours was significantly higher in the Trauma group than in the Sham group. CONCLUSION After isolated blunt renal trauma, urinary NAG levels increase in the early stage. However, more detailed clinical studies are needed to develop NAG levels as a criterion in the follow-up of blunt renal trauma.
Deneysel künt böbrek travmasında idrar n-asetil-?-D glukozaminidaz (NAG) düzeylerinin belirlenmesi
National Pediatric Urology Congress -- APR 08-10, 2010 -- Izmir, TURKEY
Keywords: NAG; renal injury; trauma